Role of Al on evolution of Non-metallic inclusions in La-bearing FeCrAl alloy - Jie Qi; Chengjun Liu; Maofa Jiang (Journal of Materials Research and Technology)
Focusing on the role of Al on the type and distribution of inclusions in Fe–Cr–Al–La alloy, based on thermodynamic analysis, the type and morphology of inclusions were observed and analyzed by SEM-EDS, the changes of number and size were counted, and the effect of Al on the evolution of inclusions was systematically analyzed. The following conclusions were obtained. Increasing Al content can inhibit the precipitation of La2O3 and promote the precipitation of LaAlO3. With the increase of La content, the critical Al content increases when La2O3 disappears completely and LaAlO3 inclusions start to precipitate. Under the same La content, when the Al content is less than 1%, the evolution rule of inclusions with the increase of heat holding time is Al2O3→La2O3+LaAlO3+La2O2S; When the mass fraction of Al increased to 2.92%, the evolution rule of inclusions is Al2O3→La2O3+LaAlO3+La2O2S→LaAlO3+ La2O2S; When the mass fraction of Al is increased to 4.96%, the evolution rule of inclusion is Al2O3→LaAlO3+La2O2S→La2O2S. When the Al content was higher than 2.92%, the precipitation of La2O3 can be effectively inhibited. With the increase of Al content, the proportion of La2O2S in the sample increases, and the particle size of inclusions decreases because of the small size of La2O2S. According to the statistical results of samples at 60min, the evolution rule of the average particle size of inclusions decreases from 1.83 μm to 1.61 μm when the mass fraction of Al increases from 0.48% to 4.96%.